Foreign Body Moves Retrograde through Ileocecal Valve during Colonoscopy - Maria Paparoupa; Markus Bruns-Toepler (Case Reports in Gastrointestinal Medicine)
Ingestion of foreign bodies and particularly of button or/and cylindrical batteries is frequent in children and adults with underlying psychiatric diseases. We present a case of a 30-year-old woman with unstable borderline disorder, where overall 4 button and 2 cylindrical batteries were endoscopically removed from her digestive system. During the last session of colonoscopy a peculiar incident was observed, as a cylindrical battery of 15 mm diameter and 43 mm length moved retrograde through ileocecal valve into the small bowel. The foreign body removal from terminal ileum was effective and safe using an endoscopic loop. This report suggests that endoscopic insertion in terminal ileum should be attempted in every colonoscopy session conducted under the indication of foreign body removal, as the possibility of retrograde movement of even large foreign bodies in the colon and through ileocecal valve is given.